Are undergraduates able to identify instances of plagiarism? / Ho Chui Chui - Ho, Chui Chui (UPENA, 2006)
This paper reports the findings from a survey on plagiarism that the author conducted among students pursuing a law foundation programme. They were administered a questionnaire with ten statements. Students were asked to identify the statements they considered as instances of plagiarism. Although a majority of the participants were able to identify most cases of plagiarism, almost half (47%) did not identify paraphrasing materials in their own words without citing the source of information as an example of plagiarism. In addition, summarising materials without indicating the source is not considered as an act of plagiarism by as many as 61% of the respondents. It is concluded that some students are probably plagiarising their assignments because they are unclear as to what constitutes plagiarism.